2019
DOI: 10.1080/14767058.2019.1594190
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with obtaining results on repeat cell-free DNA testing in samples redrawn due to insufficient fetal fraction

Abstract: Factors associated with obtaining results on repeat cell-free DNA testing in samples redrawn due to insufficient fetal fraction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
8
2
1
Order By: Relevance
“…In contrast to our results, several previous studies showed that the time interval between two blood draws was positively related to the success rate of a second NIPS [16,18] . A possible explanation for this discrepancy is that in the present study, more than half of the women underwent their first NIPS in the second trimester, which is in accordance with the NIPS guideline in China.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, several previous studies showed that the time interval between two blood draws was positively related to the success rate of a second NIPS [16,18] . A possible explanation for this discrepancy is that in the present study, more than half of the women underwent their first NIPS in the second trimester, which is in accordance with the NIPS guideline in China.…”
Section: Discussioncontrasting
confidence: 99%
“…Ashoor et al also found an inverse relationship between the fetal fraction and the maternal body weight [24]. Other authors have shown an increase of no-call cases in the group of overweight and obese mothers compared to the normal weight group [25]. In our study, the subjects of the group of no-call cases had a higher body weight than the rest of the subjects under analysis, however, no statistically significant relationship was observed between them.…”
Section: Discussioncontrasting
confidence: 50%
“…Factors related to a successful redraw in women with LFF were investigated by White et al. who found a higher probability for test success with a longer interval between blood sampling (+4% per day) and a lower probability for test success with a higher maternal weight (−1.2% per kilogram) 45 . Overall, a success rate of 53% on the second draw and a comparable rate on a third draw were found, similar to previous publications on redraw success rates 46,47 .…”
Section: Discussionmentioning
confidence: 99%